Pengalaman Keberagamaan Ibu Miskin Meninggalkan Gereja Pada Buku “Living Faith: Everyday Religion And Mothers In Poverty” - Najihah, Bannan Naelin; Truna, Dody S (AL-ADYAN, 2023)
This research reveals the causes and religious experiences of poor single mothers leaving the church in the book "Living Faith: Everyday Religion and Mothers in Poverty" by Susan Crawford Sullivan through economic, psychological, gender and theological approaches. The type of method used in this research is descriptive qualitative research with content analysis techniques and library research. The results of this study show that from the resource approach, it was found that the reasons why poor single mothers left the church were limited time resources and financial resources. From the aspect of women's social experience, various problems of discrimination and stigmatization of single mothers and poverty caused these poor single mothers to leave the church. Using the theory of self-acceptance, the poor single mothers assessed that they were poor and did not have the appropriate morals so they felt inappropriate to enter the church.  Through a theological approach, poor mothers experience a transition from institutional religion to individual religion (religious individualism) as a manifestation of religiosity in a new form.